Editor-in-Chief’s Message - Pradhan, Pratima (KEC Journal of Science and Engineering, 2026)
Editor-in-Chief’s Message Dear Readers, It is with great pride and enthusiasm that I present Volume 10, Issue I of the KEC Journal of Science and Engineering (KJSE), a significant milestone that marks a decade of our continued commitment to academic excellence and knowledge dissemination. Since its inception in 2013 under the Office of KEC Research and Publication (OKRP), KJSE has steadily evolved into a credible platform for fostering research, innovation, and scholarly dialogue within Nepal and beyond. Over the years, engineering has undergone rapid transformation, driven by advancements in artificial intelligence, sustainable technologies, data science, and interdisciplinary integration. As we step into this new volume, we reaffirm our mission to bridge theory and practice by promoting research that not only advances scientific understanding but also addresses real-world challenges. In doing so, we aim to cultivate a culture of inquiry, creativity, and responsible innovation among students, faculty, and professionals. This issue brings together a diverse collection of research articles and technical contributions that reflect the dynamic and multifaceted nature of engineering and applied sciences. The works featured herein demonstrate rigorous analysis, innovative thinking, and a strong commitment to solving contemporary problems. We are particularly encouraged by the growing participation of young researchers and students, whose curiosity and dedication continue to shape the future of engineering. As KJSE enters its tenth volume, we are also focused on strengthening our academic reach and impact in the society. Building upon our inclusion in platforms such as NEPJOL, we aspire to expand collaborations with national and international institutions, enhance the quality of peer review, and encourage interdisciplinary research that transcends traditional boundaries. We remain equally committed to engaging with industry stakeholders, recognizing the importance of practical insights and real-world applications in enriching academic discourse. I extend my heartfelt gratitude to all authors, reviewers, editorial board members, and the OKRP team for their unwavering support and dedication. Your contributions are the foundation of this journal’s success. I also encourage our readers to actively engage with the published work, share insights, and contribute to future editions. As we celebrate this milestone, let us continue to push the boundaries of knowledge, inspire innovation, and work collectively towards engineering solutions that are sustainable, inclusive, and impactful. Thank you for being a valued part of the KJSE community. Sincerely, Pratima Pradhan, PhD Editor-in-Chief KEC Journal of Science and Engineering (KJSE) Office of KEC Research and Publication (OKRP) April, 2026